Introduction to materials science for engineers - Shackelford, James F. (Pearson, 2021)
Introduction to Materials Science for Engineers offers a balanced, current treatment of the full spectrum of engineering materials. The text covers all the physical properties, applications and relevant properties associated with engineering materials. Author James Shackelford explores all major categories of materials while also offering detailed examinations of a wide range of new materials with high-tech applications. The 9th Edition has been revised to reflect recent data, trends and information. State-of-the-art computer-generated crystal structure illustrations provide the most technically precise and visually realistic illustrations available. Where appropriate, images are now presented in full color to provide a more vibrant presentation of visual information. New end-of-chapter conceptual problems throughout the text help you further your understanding of the topics presented.